Intégrité et authenticité d’un objet patrimonial numérisé : l’approche déontologique du projet Reseed - Michel Cotte (Humanités Numériques)
The article addresses the issue of the digital treatment of the integrity and authenticity of a heritage object or site and, consequently, the use and meaning of these terms within the digital process itself. Indeed, these two notions play a central role in assessing the heritage value of a property. To be rigorous and thorough a project based on reverse engineering and heritage documentation by means of digital tools cannot avoid addressing these questions. Their integration into the vocabulary of digital tools must deal with potential shifts in meaning and use the terms carefully. In this case, the complementarity that is established between the real object and its digital treatment can enrich a reasoned deontological approach to the implemented process.